FEATURES OF STOCK AND INCOMPLETE PRODUCTION ACCOUNTING IN IFRS AND SNA - M. Uspayeva (Вестник университета)
The article concerns the problems of financial reporting data use in the forming of key macroeconomic indicators. In the article the conceptual features of harmonized accounting systems are analyzed, the theoretical topics of stock and incomplete production accounting in the process of market output estimation in the System of national accounts (SNA) are considered.